Epidemiology and diagnostic methods of lumpy skin disease: A Short Review - Chala Guyassa (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Lumpy skin disease (LSD) is a severe viral disease that is having an impact on the cattle industry. The disease is now widespread in the majority of African countries, and it has lately expanded beyond the continent into the Middle East area. The disease's symptoms include an initial period of fever, followed by swollen lymph nodes, circumscribed firm skin nodules, and ulcerative lesions. It occurs in all agroclimatic situations, although it is more common in low-lying areas and beside watercourses. It is transmitted by insect vectors among cattle that share comparable pasture and watering sites and gather in the same barn. In this article, the lumpy skin disease virus, its epidemiology, and diagnostic methods are reviewed.